Chemical components and anti-inflammatory activity of the aqueous extract of the rhizomes of Kaempferia galanga L. - Mohd. Hidir, Saadiah; Ibrahim, Halijah (Malaysian Journal of Science, 2017)
Abstract. This study reports the effects of the aqueous extract of the rhizomes of Kaempferia galanga L. on rats administered intraperitoneally. The extract showed anti-inflammatory activity at doses of 30, 60 and 125mg kg-I in carrageenin-induced paw oedema, The extract at a dose of 125 mg kg-I also inhibited histamine-induced paw oedema. In peroxide-induced paw oedema, the extract at doses of 125 and 250 mg kg-I inhibited the oedema when the doses were given 20 minutes before the injection of glucose oxidase. The percentage suppression of oedema was higher at 450 mg kg-I. As the aqueous extract was also shown to have irritant property that can exert anti-inflammatory effects through a 'counter-irritant' mechanism, the the irritant nature of the extract could contibute to the observed anti-inflammatory effects